Carbon coated heterojunction CoSe2/Sb2Se3 nanospheres for high-efficiency sodium storage. Issue 15 (23rd March 2023) - Li, Gongqiang; Song, Meng; Zhang, Xiao; Sun, Yanfang; Guo, Jinxue
Abstract : Carbon coated CoSe2 /Sb2 Se3  heterojunction can effectively activate surface pseudocapacitive contribution and improve electrochemical dynamics, thus achieving high-performance anodes for sodium ion batteries. Abstract : Multicomponent metal selenides with heterostructures are believed to effectively activate the surface pseudocapacitive contribution and improve the electrochemical dynamics, thus achieving high-performance anodes for sodium ion batteries (SIBs). Herein, a carbon coated CoSe2 /Sb2 Se3 heterojunction (CoSe2 /Sb2 Se3 @C) is designed and constructed via an ion-exchange reaction between Co and Sb, and the subsequent selenization step. It is found that the hetero-structure and carbon shell effectively boost the charge transfer in the CoSe2 /Sb2 Se3 @C composite electrode. The highly pseudocapacitive Na + storage contribution is acquired due to the structural benefits of the heterojunction. Therefore, the CoSe2 /Sb2 Se3 @C anode affords good cycling stability (264.5 mA h g −1 after 1000 cycles at 2 A g −1 ) and excellent rate capability (266.0 mA h g −1 at 5 A g −1 ). This study supplies a reference for developing an advanced anode with multicomponent and heterojunction structures for energy storage.